Decompressive Hemicraniectomy Associated With Ultrasound-Guided Minimally Invasive Puncture and Drainage Has Better Feasibility Than the Traditional Hematoma Evacuation for Deteriorating Spontaneous Intracranial Hemorrhage in the Basal Ganglia Region: A Retrospective Observational Cohort Study - Cheng, Yuan; Chen, Jin; Zhao, Guanjian; Xie, Zongyi; Huang, Ning; Yang, Qiang; Chen, Weifu; Huang, Qin (Frontiers in Neurology, 2021)
objectives Spontaneous intracerebral hemorrhage (ICH) is a devastating disease with higher mortality and disability rates, however, the ideal surgical management is still to be determined for critical ICH. The purpose of this study was to prove the feasibility and unique clinical value of a novel combination, decompressive hemicraniectomy associated with ultrasound-guided minimally invasive puncture and drainage (DH+MIPD), for deteriorating ICH in the basal ganglia region.Methods According to the enrollment criteria, 168 ICH patients were analyzed retrospectively, of which 86 patients received DH+MIPD and 82 patients received DH associated with the traditional hematoma evacuation, as the control group. The change process of hematoma, perihematoma edema, and intracranial pressure (ICP) in a period of time after operation, the shortterm and long-term therapeutic effect were compared.The DH+MIPD method could effectively achieve the evacuation rate of hematoma up to 87% on 5 day post-operation and had the significant advantages of minimal injury to cerebral tissue, lighter edema degree, better effect of decreasing ICP, shorter operation time, less blood loss and lower mortality, compared with the control method. The DH+MIPD group had significantly higher survival rate within 1 year post-operations (P = 0.007) and better functional outcome on 90 day and 180 day post-operations (P= 0.004). And subgroup analysis pointed out that DH+MIPD method had a definite survival advantage for critical ICH patients, older＞ 60 years old and with hematoma located in the left dominant hemisphere.Conclusions Our results proved the feasibility of DH+MIPD on hematoma evacuation and realized the hypothesis of reducing mortality and improving functional recovery. This method provides one more choice for individualized therapy of ICH in the basal ganglia region.